Att läsa människor: Om litteraturläsning i läkarutbildningen - Petersson, Margareta; Årheim, Anette (Tidskrift för litteraturvetenskap, 2010)
Reading Literature in Medical Education In the several professional educations where human encounters are important in the professional practice, the theoretical curriculum is today completed with fiction. Medical education is an example and since the 1970s the so called medical humanities have had a great impact. Doctors need developing the clinical judgment and here, the representatives claim, the encounter with literary characters, might fill the gap between theory and practice. From an empirical material we discuss in this article some aspects of the use and function of fiction at one of the medical educations in our country where doctors interested in fiction conduct the seminars. The results show that literary characters are understood as human beings; through identifying with a character you are supposed to widen and deepen your knowledge of human beings. The students are encouraged to emotional involvement in stories and to make ethical standpoints. A fact complicating the results in our investigation is that the students’ literary competence does not correspond to what the conductors expect. The literary course is also lacking long term strategies. The results each course reaches thus depend on individual conductor’s interests and reading strategies.